Dexamethasone and p38 MAPK inhibition of cytokine production from human lung fibroblasts. (14th November 2020) - Higham, Andrew; Singh, Dave
Abstract: Lung fibroblasts are involved in airway inflammation and remodelling in COPD. We report an investigation of the effects of combining a p38 MAPK inhibitor with a corticosteroid on cytokine production by a human lung fibroblast cell line and primary fibroblasts obtained from human lung tissue. Our main interest was to determine whether additive or synergistic anti‐inflammatory effects would be observed. We observed inhibition of IL‐6 and CXCL8 secretion from both lung fibroblast models by dexamethasone (maximal inhibition 40–90%) and the p38 MAPK inhibitor BIRB (maximal inhibition 30–60%), used alone and evidence of increased anti‐inflammatory effects when used in combination. This combination effect was more apparent for TNF‐a stimulated cytokine production (maximal inhibition increased by 10–20%). Interaction ratio analysis showed this enhanced effect to be additive rather than synergistic interaction. Similar results were obtained using both fibroblast cell culture models. Combining a p38 MAPK to corticosteroids may help reduce fibroblast mediated inflammation in COPD.